The Zion Christian Church (ZCC) in the Light of the Understanding of Scripture by the Reformation - Kruger, M. A. (In die Skriflig/In Luce Verbi, 1983)
The theme of this paper asks for an appraisal of the ZCC. The appraisal of criticism must be done from the point of view of the understanding of Holy Scripture by the reformers. The ZCC has in its name the word church. Our aim will thus be to ascertain whether the ZCC complies with the marks of the true church or how far it is in agreement with these marks as they have been pointed out by the Reformation.
free
Keywords: Calvin; Jean; 1509-1564; Church – Marks; Zion Christian Church